2013
DOI: 10.1093/schbul/sbt147
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for Corticostriatal Dysfunction During Cognitive Skill Learning in Adolescent Siblings of Patients With Childhood-Onset Schizophrenia

Abstract: Patients with schizophrenia perform poorly on cognitive skill learning tasks. This study is the first to investigate the neural basis of impairment in cognitive skill learning in first-degree adolescent relatives of patients with schizophrenia. We used functional magnetic resonance imaging to compare activation in 16 adolescent siblings of patients with childhood-onset schizophrenia (COS) and 45 adolescent controls to determine whether impaired cognitive skill learning in individuals with genetic risk for schi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 62 publications
1
15
0
Order By: Relevance
“…In this study, Wagshal et al demonstrated that healthy siblings of COS patients showed aberrant frontal and striatal activation relative to healthy controls during a cognitive skill learning task (Wagshal et al, 2014). Activation was measured throughout learning, and healthy siblings demonstrated increased frontal activation during an initial slow learning period and then decreased activation after training (Wagshal et al, 2014). The striatal activation in healthy siblings was also different from controls, decreasing steadily throughout the learning process instead of remaining constant over time (Wagshal et al, 2014).…”
Section: 4 Healthy Siblingsmentioning
confidence: 64%
“…In this study, Wagshal et al demonstrated that healthy siblings of COS patients showed aberrant frontal and striatal activation relative to healthy controls during a cognitive skill learning task (Wagshal et al, 2014). Activation was measured throughout learning, and healthy siblings demonstrated increased frontal activation during an initial slow learning period and then decreased activation after training (Wagshal et al, 2014). The striatal activation in healthy siblings was also different from controls, decreasing steadily throughout the learning process instead of remaining constant over time (Wagshal et al, 2014).…”
Section: 4 Healthy Siblingsmentioning
confidence: 64%
“…The WPT was a probabilistic classification task adapted from Wagshal et al (19). The WPT consisted of 320 trials during which participants predicted the weather based on cue combinations that probabilistically related to "sun" and "rain."…”
Section: Methodsmentioning
confidence: 99%
“…We examined the effects of augmenting NMDAR signaling on two indices of experience-dependent plasticity: (i) LTP and (ii) incremental learning. Participants completed the visual LTP task using high-frequency visual stimulation (HFvS) to induce potentiation of visual cortex neurons, followed by a weather prediction task (WPT) (19), an information integration task (IIT) (20), and an n-back task. The WPT and IIT are incremental learning tasks in which stimulusfeedback associations are thought to be encoded by LTP at corticostriatal synapses (21,22).…”
mentioning
confidence: 99%
“…An analysis was also conducted on a subset of these subjects (ten siblings of COS patients and forty-three controls) to investigate if these differences were related to WPT performance (accuracy). Behavioral data from the subjects in these analyses overlap with our previous studies describing group effects that used different neuroimaging modalities in siblings of COS patients (Wagshal et al, 2015(Wagshal et al, , 2012(Wagshal et al, , 2013.…”
Section: Participantsmentioning
confidence: 70%
“…Performance on the WPT is impaired in patients with schizophrenia (Foerde et al, 2008;Horan et al, 2008;Keri et al, 2005;Weickert et al, 2002) and their adult and adolescent relatives (Wagshal et al, 2012;Weickert et al, 2010). In addition, in previous fMRI and volumetric studies (Wagshal et al, 2015(Wagshal et al, , 2013 examining a subset of these subjects, we have also demonstrated the COS siblings showed a relative deactivation in frontal and striatal regions, as well as in the cerebellum, compared to controls after extensive training on the WPT and that poorer performance in later learning on the WPT was related to a smaller volume in the cerebellum in COS siblings.…”
Section: Introductionmentioning
confidence: 95%